2015
DOI: 10.1074/jbc.m115.650978
|View full text |Cite
|
Sign up to set email alerts
|

Gα13 Switch Region 2 Binds to the Talin Head Domain and Activates αIIbβ3 Integrin in Human Platelets

Abstract: Background: Switch Regions of G protein G␣ subunits activate downstream cell signaling events. Results: G␣ 13 Switch Region 2 forms a calcium-dependent bi-molecular complex with the head domain of talin. Conclusion: Binding of the G␣ 13 to the talin head domain promotes ␣IIb␤3 integrin activation. Significance: These results provide a new paradigm for inside-out signaling and ␣IIb␤3 integrin activation in platelets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
14
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 31 publications
5
14
0
Order By: Relevance
“…Furthermore, a single amino acid mutation of talin's head domain, M319A, increases integrin activation compared with both wild type fulllength GFP-talin and GFP-THD (15,31). Additionally, it was shown that the co-transfection of GFP-talin with G␣ 13 , but not SR2 mutants R227A or R232A, increased integrin activation (27). These observations suggest that GFP-talin is partially, if not completely, autoinhibited when overexpressed in this model cell system.…”
Section: G␣ 13 Sr2 Binds To F3 Lobe Within the Ferm Domain Ofmentioning
confidence: 62%
See 4 more Smart Citations
“…Furthermore, a single amino acid mutation of talin's head domain, M319A, increases integrin activation compared with both wild type fulllength GFP-talin and GFP-THD (15,31). Additionally, it was shown that the co-transfection of GFP-talin with G␣ 13 , but not SR2 mutants R227A or R232A, increased integrin activation (27). These observations suggest that GFP-talin is partially, if not completely, autoinhibited when overexpressed in this model cell system.…”
Section: G␣ 13 Sr2 Binds To F3 Lobe Within the Ferm Domain Ofmentioning
confidence: 62%
“…Previously, the G protein subunit G␣ 13 has been shown to engage its SR1 to directly bind to p115RhoGEF thus increasing RhoA activity leading to cytoskeletal rearrangements (25). Recently, our group reported that G␣ 13 SR2 (where SR2 is one of three conformationally sensitive switch regions present in G␣ subunits) directly binds to talin and thereby modulates platelet integrin ␣IIb␤3 activation (27). This finding provided the first evidence for a G␣ 13 /talin interaction and thus represented a novel regulatory pathway.…”
mentioning
confidence: 75%
See 3 more Smart Citations